Analisis Kebijakan Program Menghafal Hadits di MTs Asnawiyah dalam Membentuk Karakter Religius Siswa - Resmi, Mega Mesra; Khasanah, Nur; Khadijah, Khadijah; Syarif, Marhamah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the policy of the hadith memorization program at MTs Asnawiyah, Bogor, in shaping the religious character of students. The research method used is quantitative with a simple linear regression approach. Data was collected through a questionnaire questionnaire with a Likert scale of 1-5, which was distributed to 20 students as respondents. The independent variable in this study is the policy of the hadith memorization program, while the bound variable is the religious character of the students. The results of the analysis showed that there was a positive relationship between the policy of the hadith memorization program and the formation of students' religious character, with a regression coefficient of 0,65. This shows that every improvement in the implementation of the hadith memorization program policy contributes by 65% to the improvement of students' religious character. In addition, the significance value obtained is below 0.05, which indicates that the relationship is statistically significant. Based on these findings, it can be concluded that the hadith memorization program at MTs Asnawiyah, Bogor, is effective in shaping the religious character of students. Therefore, it is recommended that this policy continue to be improved, by paying attention to aspects of teacher training, supporting facilities, and student motivation in memorizing hadiths.